“Italian Contemporary Architecture” (1952-1955). Riflessioni su una mostra e sulle pratiche espositive per l’architettura nel dopoguerra - Cordera, Paola (Lo sguardo rinnovato, 2026)
This essay focuses on the “Italian Contemporary Architecture” exhibition, held in 1952 at the Royal Institute of British Architects in London, as a pivotal moment in the postwar cultural and architectural context. Framed at the intersection of historical narrative and curatorial experimentation, the exhibition presented a selection of key Italian architectural works from 1930 to 1951. Drawing on the exhibition catalogue, periodicals, and unpublished archival sources, the essay reconstructs the complex critical and curatorial framework of the exhibition, situating it within broader postwar exhibition practices conceived as tools of cultural mediation and identity construction. It also highlights the set up of a specific exhibition format and the show’s international circulation in Paris (1954), Livorno (1954), and Florence (1955), as well as less familiar iterations in Stockholm and Helsinki. Together, these aspects attest to how the exhibition operated as a platform for Italian architecture, and as a tool for shaping and projecting a national image abroad.